Determining the clonality and significance of coagulase-negative staphylococci isolated from blood cultures in HUSM - Hamzah, Siti Hawa (2010)
Coagulase-Negative Staphylococci (CoNS) is a group of microorganisms that are increasingly implicated as a cause of significant infection and has emerged as the most frequent cause of nosocomial bloodstream infection. CoNS species are nonnal skin flora and, it can be difficult to determine if CoNS species isolated from blood cultures reflect infection or microbial contamination. At the moment, pulsed-field gel electrophoresis (PFGE) is considered as a gold standard to diagnose the significance of CoNS isolated from blood cultures. In this study, significance of repeated CoNS isolated from blood cultures were evaluated by species identification, antibiogram and a molecular method, PFGE. A total of 101 pairs of Coagulase-Negative Staphylococci were analyzed during this period of study. These isolates were identified to the species level by API Staph ID. Out of 101 pairs(, only 84 pairs (83.1%) of CoNs identified were similar species. These 84 pairs were further analyzed by pulsed-field gel electrophoresis (PFGE) to detennine its clonality (genotypic). However only 33 pairs had eligible PFGE result for interpretation In this study, Staphylococcus epidermidis was the predominant species isolated (52.5%), followed by S.capitis (10.4%) and S.chromogenes (1.9%). The percentage of methicillinresistant CoNS was higher (68.68%) as compared to methicillin-sensitive CoNS. The percentage of same phenotype with same antibiogram pattern (40.7%) was lower as compared to same phenotype and different antibiogram pattern (59.3%). There was a significant association between same phenotype and same antibiogram pattern. Out of 33 pairs of CoNS analyzed, 87.9% (29 pairs) had indistinguishable patterns which denote the same bacterial strains. However the association between phenotypic and genotypic cannot be made because due to failure to maintain reproducible PFGE results, hence resulted in insignificant statistical findings. Overall laboratory concordance case was defined as a case which were concordant for the triple tests conducted: phenotypic, antibiogram pattern and genotypic. Out of 33 pairs of CoNS with PFGE results, 14 cases (42.4%) were concordant cases which represent laboratory true bacteraemia and 19 cases (57.6%) were regarded as contaminants. In this study, there was significant association between same phenotype and antibiotic treatment. The percentage of those who had antibiotic treatment and same phenotype was higher (90.9%) as compared to those without antibiotic treatment (9.1%). There was significant association for leukocyte count, nosocomial infection and antibiotic treatment with antibiogram pattern. The association of laboratory concordance cases with clinical parameters showed significant association between laboratory concordance cases with blood pressure, leukocyte count and antibiotic treatment. All clinical parameters were not significantly associated with concordance genotype. The outcome of this study showed that genotype by pulsed-field gel electrophoresis (PFGE) failed to show any association with clinical bacteraemia by statistical calculation due to small sample size